Kajian Model Angkutan Sedimen pada DAS Serayu Berdasarkan Model Matematik 1 Dimensi - Kusuma, M. Syahril Badri; Salim, Hang Tuah; Gusman, Aditya Riadi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
This paper present comparisonÂ  study of several mathematical model for sediment transport, e.g. Yang (1973), Ackers-White (1973), Madden (1963), Vanony-Duboys (1975), Schocklitsh-Toffaleti (1966), Meyer-Peter-Muller (1948) dan Colby (1964). The study was supported by 1 dimensional mathematical model named HEC6. Model Calibration and verification were done by using field data measurement that was taken at Mrica Reservoir in 1992-1993 and 2002-2003. Based on this study, it is found that the best assessment for the sedimentation process in the upstream of the reservoir is shown by Yang model (1973), meanwhile the best assessment for the sedimentation process in the downstream of the reservoir is shown by Colby model (1964).Keywords: sediment transport, one dimension mathematical model, Serayu riverPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3952[How to cite: Kusuma, M.S.B., Salim, H.T. dan Gusman, A.R., 2006, Kajian Model Angkutan Sedimen pada DAS Serayu Berdasarkan Model Matematik 1 Dimensi, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 3, pp. 260-276]